New fluorinated diamond microelectrodes for localized detection of dissolved oxygen - Silva, Eduardo
The present work reports on a novel needle type oxygen microsensor based on boron doped diamond (BDD) with tailored surface aiming in better electrochemical performance. The microelectrodes are produced by growing diamond films using HFCVD (hot filament chemical vapor deposition) on top of electrochemically sharpened tungsten filaments. The diamond is functionalized using CF4 RF-plasma post-treatments resulting in fluorine termination of the surface. The quantitative detection of the dissolved oxygen (DO) is demonstrated and supported with successful fitting to the theoretical values calculated for diffusion limited current on hemicylinder shape electrode. The developed MEs were calibrated and tested as probes for microamperometric mapping of dissolved oxygen in a Zn-Fe wire-electrode model galvanic couple immersed in 50 mM NaCl. Modified diamond MEs show a fast and stable response towards oxygen mapping, as well as stability for several days of measurements. (C) 2014 Elsevier B.V. All rights reserved.